1999
DOI: 10.1046/j.1365-2133.1999.02897.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet irradiation induces cyclooxygenase-2 expression in keratinocytes

Abstract: We examined the effect of ultraviolet (UV) irradiation on the expression of cyclooxygenases in cultured HaCaT keratinocytes and in human skin in vivo. UVB irradiation (10 and 50 mJ/cm2) and hydrogen peroxide (200 micromol/L) increased cyclooxygenase-2 mRNA expression in HaCaT keratinocytes. No clear expression of cyclooxygenase-1 mRNA was detected in either control or stimulated HaCaT cells. Genistein, a tyrosine kinase inhibitor, suppressed both the basal and stimulated expression of cyclooxygenase-2 in HaCaT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
1
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 36 publications
4
72
1
2
Order By: Relevance
“…We found that COX-2 mRNA and protein were increased in mouse keratinocytes following UVB exposure. These data are consistent with earlier reports showing that UVB effectively induces COX-2 in mouse and human keratinocytes (Isoherranen et al, 1999;Black et al, 2008). Our data also demonstrate that differentiated cells are more sensitive to UVB-induced upregulation of COX-2 mRNA and protein, a finding consistent with previous studies showing that UVB-induced COX-2 expression in mouse skin occurs primarily in the suprabasal, differentiated keratinocytes (Athar et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that COX-2 mRNA and protein were increased in mouse keratinocytes following UVB exposure. These data are consistent with earlier reports showing that UVB effectively induces COX-2 in mouse and human keratinocytes (Isoherranen et al, 1999;Black et al, 2008). Our data also demonstrate that differentiated cells are more sensitive to UVB-induced upregulation of COX-2 mRNA and protein, a finding consistent with previous studies showing that UVB-induced COX-2 expression in mouse skin occurs primarily in the suprabasal, differentiated keratinocytes (Athar et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…Metabolism of PGH 2 leads to the generation of PGD 2 , PGE 2 , PGF 2 , PGI 2 and thromboxane A 2 which are synthesized by PGD 2 synthase, PGE 2 synthase, PGF 2 synthase, PGI 2 synthase and thromboxane A 2 synthase, respectively (Helliwell et al, 2004). Exposure to UVB light, which is known to cause cutaneous inflammation and cancer (Hruza and Pentland, 1993), has been reported to upregulate COX-2 in human and mouse skin (Buckman et al, 1998;Isoherranen et al, 1999;Chen et al, 2001;Bachelor et al, 2005), a process linked to many of its biological effects (Fitzpatrick, 2004). Increased concentrations of PGE 2 , PGF 2α and PGD 2 have been detected in UVB-exposed skin (Black et al, 1980a) and, in cultured keratinocytes, PGE 2 is the predominant prostaglandin identified following UVB exposure (Miller et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Soriani et al (1998) previously showed that UVA-induced COX-2 mRNA expression was decreased by epigallocatechin in the human oral carcinoma cell line KB but not in the human skin fibroblast cell line FEK4. Induction of COX-2 mRNA was also reported in response to solar simulated irradiation of human skin (Isoherranen et al, 1999). At this time, however no study has addressed the role of the UVA spectrum alone in the expression of COX-2 in a model of nonmelanoma skin cancer.…”
Section: Introductionmentioning
confidence: 96%
“…UVB induced COX-2 expression in human skin (Buckman et al, 1998;Isoherranen et al, 1999), and oral administration of selective COX-2 inhibitor, celecoxib, produced a decrease in the tumor number and multiplicity in UV-treated hairless mice (Pentland et al, 1999). In view of the importance of COX-2 in UVB-induced tumorigenesis, we have begun to characterize the signaling pathway of UVB induction of COX-2 in human keratinocytes, HaCaT (Chen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%